Maqāṣid Syariah sebagai Paradigma Holistik dalam Pengembangan Civic Education Kontemporer - Asih Wahyu Rini; Syamsuddin; Alfiah Ratu Balqis; Afriantoni (Journal of Innovative and Creativity, 2025)
Contemporary civic education faces a range of complex challenges amid globalization, modernity, and increasing societal pluralism. These phenomena have led to value shifts, identity fragmentation, and a weakening of citizens’ moral orientation. In many educational contexts, civic education tends to emphasize cognitive and legalistic aspects, while ethical, spiritual, and humanistic dimensions receive less attention. This situation creates an urgent need for a new paradigm capable of integrating values, morals, and civic competencies in a more comprehensive manner. In this context, maqāṣid al-sharī‘ah offers a holistic normative framework that can enrich the orientation of civic education. Maqāṣid al-sharī‘ah, the fundamental objectives of Islamic law, encompass five core principles—protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). These principles not only serve as ethical foundations within Islam but also resonate with universal values in modern civic education, such as human dignity, justice, rationality, family integrity, and socio-economic ethics. This article examines maqāṣid al-sharī‘ah as a holistic paradigm for developing contemporary civic education. Using a literature review and normative analysis approach, this study explores classical and contemporary literature on maqāṣid al-sharī‘ah, as well as recent developments in civic education pedagogy. The literature review method is employed to identify the relevance of maqāṣid values within modern educational contexts, while normative analysis is used to formulate ethical principles that can be integrated into civic education design. The analysis also includes policy review to reveal substantial opportunities for integrating Islamic values constructively into civic education curricula without reducing their universal orientation. The findings indicate that maqāṣid al-sharī‘ah plays a strategic role as a paradigm that not only affirms moral values but also provides evaluative direction for the development of civic education. The principle of ḥifẓ al-dīn offers spiritual and ethical grounding for citizens; ḥifẓ al-nafs reinforces humanistic values, the right to life, and social safety; ḥifẓ al-ʿaql highlights the importance of literacy, critical reasoning, and intellectual development; ḥifẓ al-nasl fosters awareness of social and familial responsibility; while ḥifẓ al-māl instills economic ethics, distributive justice, and public integrity. Integrating these five principles results in a civic education model that shapes not only civilly competent citizens but also moral, empathetic, and socially responsible individuals. In conclusion, maqāṣid al-sharī‘ah can serve as a holistic and constructive paradigm for strengthening contemporary civic education. By integrating spiritual, moral, and social values, this paradigm offers a renewed orientation for civic education that is more humanistic, inclusive, and responsive to the dynamics of the times. The integration of maqāṣid al-sharī‘ah into civic education has the potential to enhance social justice, moral integrity, and active citizen participation within democratic life.